SPP PAYMENT SYSTEM DATA PROCESSING IN JAKARTA SMK 33 PGRI - Fithonah Fithonah; Eko Hadiyanto, SSi, MM (Jurnal Sistem Informasi, 2002)
A good information system will be useful in carrying out the functions of decision making by presenting data and precise information, the authors draw the following conclusion: 1. Process of reporting a more rapid, accurate and efficient. 2. With the existence of more complete information, quickly and accurately can helpÂ Â  the management in making decisions and know the development of SPP payment school administration through reports presented.